Factors Related to Mental Health During the COVID-19 Lockdown in Spain - Pinedo, Ruth; Vicario-Molina, Isabel; González Ortega, Eva; Palacios Picos, Andrés (Frontiers in Psychology, 2021)
The COVID-19 disease has forced governments to adopt exceptional measures. The lockdown decreed in Spain in 2020 required citizens to stay confined at home, which might have affected their mental health. The objective is to identify factors that influenced adults’ mental health during this period. A sample of 3,508 adults from the Spanish general population completed an online survey that collected sociodemographic data and information about daily planning and activities, healthy habits, loneliness, coping humor and mental health. Data were analyzed using Structural Equation Modeling. According to the results, the proposed model showed good fit values, and latent variables explained 30% of the variance in mental health. Loneliness, coping humor, healthy habits, age and gender had a significant weight in the prediction of mental health during lockdown. Area of residence, number of days of confinement and number of people in the household were not related to mental health. This study addresses the effect of COVID-19 and social distancing measures by identifying risk and protective factors for the development of mental health difficulties. There is a need to target specific and early interventions aimed at mitigating the psychological impact of the pandemic while increasing wellbeing, especially in more vulnerable groups